FUNDAMENTAL PROPERTIES AND EXAMPLES OF CLASS USAGE IN THE PYTHON PROGRAMMING LANGUAGE - Saidaxmedov Eldor Islomovich; Boboyorov Novruzbek Inotullayevich; Nabiyev Raxim Azamatovich (Bright Mind Publishing, 2025)
Classes in the Python programming language are a central concept of object-oriented programming. This article explores the fundamental characteristics of classes, including attributes for storing data and methods for defining behavior. It also provides practical examples of creating classes, instantiating them (creating objects), and using them to solve various programming problems. Important principles of object-oriented programming such as inheritance, polymorphism, and encapsulation are also analyzed in detail. Throughout the article, the significance of classes in the software design and development process is demonstrated through real-life scenarios
Keywords: Python Classes, Object-Oriented Programming (OYD), Attributes, Methods, Objects, Instantiation, Inheritance, Polymorphism, Encapsulation, Abstraction, Software Design.